AUTHORITARIAN PARENTING STYLE WITH AGGRESSIVE BEHAVIOR OF 5-6 YEARS OLD - Defanny Fauziyah Pratiwi; Ruli Hafidah; Adriani Rahma Pudyaningtyas (Early Childhood Education and Development Journal, 2019)
The family is the place where the education process takes place. Parents hold the first and foremost role for child development which is an important task and cannot be separated from various challenges. Parenting style is one of the behavioral factors and actions of children since early to adulthood. The purpose of this study was to determine the relationship between authoritarian parenting and the aggressive behavior of children aged 5-6 years. Sampling using purposive sampling technique amounted to 37 parents and children aged 5-6 years in Mojolegi, Teras, Boyolali. Data in this study were obtained from questionnaires. The technique of analyzing questionnaire items using the total corrected item-total correlation. The results showed that there was a significant relationship between authoritarian parenting and the aggressive behavior of children with r = 0.996 with p = 0.000 with the help of SPSS 16 for windows. This value shows a positive result which means that the higher the authoritarian parenting style, the higher the child's aggressive behavior.